Critical analysis of the justification and economic fundamentals of the intellectual property rights system - Márquez Escobar, Carlos Pablo (2005)
The author claims that, from a general perspective, the economic analysis of infonnation and its relation with law presents a strong inefficiency. The author develops a study ofthe economic incentives in general and the manner how prívate property is constituted as the principal but is not the only one of the economic incentives for the production of information and innovation. In strict sense, the author explores the ontology of property, showing that it does not allow the inclusion of immaterial and intangible goods since the modern fundamentals of such institution come form the appropriation and the homesteading rule, categories incompatible with the ontology of information. Into such argumentation, the author studies the economic incentive theories for information and innovation, initiating with the study of the characters of information and the fallacies that always had surrounded such good. The author concludes showing that intellectual property rights are not the product of an evolutionary process, but, on the contrary, they come from privileges conceded by the State, which its justification and fundament is invalid and equivocal due to the incompatibility of the property and the homesteading rule with the ontology of information.